Herd effect and retail investors' behavior in the Palestine exchange - Alaraj, Muath (Edelweiss Applied Science and Technology, 2025)
This study aims to analyze the presence and impact of the herd effect in the Palestine Exchange (PEX). By utilizing the cross-sectional standard deviation (CSSD) methodology on pooled cross-sectional data, the research investigates whether investor behavior exhibits characteristics of a herd mentality and how this affects market efficiency. The findings reveal that herd mentality alone is insufficient to produce a significant herd effect in PEX. Furthermore, record market return fluctuations do not result in significant market anomalies within this context. The results suggest that the presence of herd behavior does not translate into impactful market outcomes in PEX. The market structure and investor dynamics may limit the manifestation of strong herding patterns, despite observable behavioral tendencies. These findings have important policy implications, offering policymakers a more skeptical notion of the PEX as an inefficient market. Additionally, the study contributes to the literature by producing empirical outcomes that are committed to the specific context of PEX.